Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, Pertumbuhan Penjualan Dan Dividend Payout Ratio Terhadap Struktur Modal (Studi pada Perusahaan Property dan Realestate yang terdaftar di BEI tahun 2013-2017) - Rahmadani; Putra Ananto, Rangga; Andriani, Wiwik (Akuntansi dan Manajemen, 2019)
This study aims to determine the effect of profitability, liquidity, firm size, sales growth, and dividend payout ratio on capital structure. The sampling technique uses purposive sampling method so that a sample of 28 property and realestate companies are listed on the Indonesia Stock Exchange during the 2013-2017 period. The type of data used is secondary data in the form of annual financial statements of property and realsetate companies in 2013-2017. Data analysis method used is multiple linear regression analysis using SPSS version 20. The results of this study indicate that partially profitability proxied by net profit margin (NPM) does not affect the capital structure, liquidity is proxied by the current ratio (CR) effect on the capital structure, the size of the company which is proxied by total assets (Ln TA) does not affect capital structure, sales growth that does not affect the capital structure, dividend payout ratio does not affect the capital structure. Simultaneously profitability, liquidity, company size, sales growth and dividend payout ratio affect the capital structure